Urban space and politics of the everyday: thinking through and with the image in contemporary Cairo - Spirk, Darren (AUC Knowledge Fountain, 2020)
This thesis addresses the increasing eminence of the image within contemporary social theory to intervene into what Tarek Elhaik terms the “sensorial turn” in anthropology. I implement a method of thinking through and with the image that balances creative and critical modalities of engaging socially embedded images beyond a semiotic approach. My entryway into such discussions is seven Cairo films from 2010-2013 that allow us to complicate “pre-” and “post-” revolutionary imaginaries and expand how to see, listen to, and think the political everyday and changing notions of publicness within the city. In tandem with the generative strategies of visual refusal in Maha Maamoun’s 2026, this thesis calls for re-approaching the visual in Cairo through an urban spatial focus on the present everyday-lived. In moving to the films Al-baḥth ‘an madīna, Karim, Cairography, Al-khurūg lil-nahār, Qaṣ, and Al-shuhub tudhakarunī bil-mutanaṣṣitīn, the thesis weaves deep descriptions of their images across various spatiotemporal contexts with distinct theoretical arguments relevant both to this period and the difficult horizon facing Cairo today. Through an embodied form of creative anthropological writing, I engage urban and visual culture scholars, as well as other social theorists, to perform the following: highlight long-standing and constitutive intersections of space and subjectivity otherwise to the global “imagining” of collective action in Tahrir; track how material spaces in the image open to ever-changing and contingent nodes of potentiality and violence in the politicized urban everyday; and read challenging liminalities of public and private space—at critical intersections of the aural and visual—within mundane images of eavesdropping. Ultimately, this project embraces a partiality of knowing that incorporates not only the particular contributions of this contemporary Cairo context but also a decolonial ethos from an urban global south perspective into emerging anthropologies of the image.